PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM INFORMASI, DAN KUALITAS TEKNOLOGI INFORMASI TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL - Komang Adhi Rivan Niagawan; Ni Putu Yeni Yuliantari; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2020)
The purpose of this study was to determine the effect of human resource competence, information systems and quality of information technology on the application of accrual-based government accounting standards. The sample used in this study were 93 people. The data analysis techniques used in this study were the validity test, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. obtained a regression coefficient value of 0.680 and sig 0.000. (2) the information system has a significant positive effect on the application of SAP, where the regression coefficient value is 0.767 and sig 0.001. (3) IT quality has a significant positive effect on the application of SAP, where the regression coefficient value is 0.719 and sig 0.000 (4) simultaneously HR competence, information systems and IT quality on SAP implementation, where the F value is 96.808 and the significance is 0.000. The amount of influence of the independent variables on the application of SAP is 75.8%.